Choosing between multiple regional trade agreements: Evidence from Japan's imports. Issue 2 (16th January 2019) - Hayakawa, Kazunobu; Urata, Shujiro; Yoshimi, Taiyo
Abstract: Mega‐regional trade agreements (RTAs) are likely to overlap with other RTAs. When such overlaps occur, firms must choose the tariff rates from multiple RTAs. By employing data on Japan's imports by tariff schemes, we investigate how RTA tariff rates affect firms' decisions on tariff schemes when multiple RTAs exist. Our finding is that RTA utilization rates are higher when tariff rates for that RTA are lower (own effect) and tariff rates for alternative RTAs are higher (cross effect). We also found that the absolute magnitudes of own and cross effects are larger in bilateral and multilateral RTAs, respectively.